The lovely bones [videorecording (DVD)] - Jackson, Peter, 1961-; Jackson, Peter, 1961-; Jackson, Peter, 1961-; Ronan, Saoirse, 1994-; Wahlberg, Mark, 1971-; Weisz, Rachel, 1971-; Sebold, Alice (Paramount, 2024)
After a fourteen-year-old girl is murdered, she reaches out from the afterlife to help her family find her killer and move on with their lives.